E-COMMERCE : PENGEMBANGAN MODEL PERNIAGAAN MENGGUNAKAN INTERNET - Muh. Fachrul S (AkMen JURNAL ILMIAH, 2011)
Information systems-based e-Commerce is very important in the development of business or commerce. The purpose of this website is to introduce that one form of modern commerce model by utilizing cyberspace as a medium. This study aims to build a website on the store. This website was developed using the software Macromedia Dreamweaver 8, Apache 2.2.3, PHP 5.2 and MySQL 5.0, this website serves to provide facilities in the sale of non-food product and store information on customers wherever located